Peranan Kesesuaian Bioaktivator untuk Meningkatkan Kandungan Basa-Basa Pada Kompos Guano dan c. Odorata - Jamilah, Jamilah (Jurnal Embrio, 2009)
The experiment of bioactivator adaptive in rise of base content at guano and C.odorata compost had finished in padang during 1.5 months. The goal of study was to get the kind of the exactly of bioactivator in effort to rise the bases content in the compost. The experiment arranged in complet random in 4 treatment and 3 repeat. The treatment compost application namely; Guano + Gulma C. odorata (A); Guano + Gulma C. odorata + Biocom (B); Guano + Gulma C. odorata + Trichoderma (C); Guano + Gulma C. odorata + EM4 (D). The parameter examined were bases content analysis; K( %), Ca (%), Mg (%), Na (%), and pH. The result proved that EM4 (effective microorganisme 4) application able to increase Ca and Mg compost content highly significant and higher than another bioactivator like Biocom and Trichoderma or without bioactivator.